Effect of spray volume and application frequency on insecticide efficacy against western flower thrips (Frankliniella occidentalis) and citrus mealybug (Planococcus citri) under greenhouse conditions - Radosevich, Devin (Kansas State University, 2020)
Western flower thrips, Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), and citrus mealybug, Planococcus citri (Risso) (Hemiptera: Pseudococcidae), are major insect pests of greenhouse-grown horticultural crops. Both insect pests cause direct and indirect damage by feeding on plant leaves, stems, flowers, and fruits, which can lead to greenhouse producers experiencing significant economic losses. Insecticides are the primary management strategy used against these insect pests. Experiments were conducted under greenhouse conditions to determine the effect of spray volume and application frequency on insecticide efficacy against citrus mealybug on coleus (Solenostemon scutellarioides) and transvaal daisy (Gerbera jamesonii) plants and western flower thrips on transvaal daisy cut flowers. Three different spray volumes, two application frequencies (one or two applications), and three insecticides, each with a different mode of action, were evaluated for each insect pest. In the citrus mealybug experiments, the insecticides acetamiprid, flonicamid, and cyfluthrin were used. The 75 mL spray volume consistently resulted in a higher mean citrus mealybug mortality than the 15 or 25 mL spray volumes. In two of the spray volume experiments, each spray volume resulted in mean citrus mealybug mortalities that were significantly different from each other. Mean percent citrus mealybug mortality was significantly higher after two insecticide applications (51.2% in the second experiment and 42.7% in the third experiment) than after one insecticide application (40.3% in the second experiment and 36.1% in the third experiment). Overall, acetamiprid was more effective against citrus mealybugs, based on percent citrus mealybug mortality, than flonicamid or cyfluthrin. Acetamiprid applied at 75 mL resulted in >70% mean citrus mealybug mortality in three of the spray volume experiments. In contrast, flonicamid and cyfluthrin each resulted in <50% mean citrus mealybug mortality in all experiments. In the western flower thrips experiments, the insecticides spinosad, chlorfenapyr, and flonicamid were used. In general, mean western flower thrips adult mortality increased as the spray volume of each insecticide increased. Application frequency affected western flower thrips adult mortality with spinosad resulting in 100% mortality and chlorfenapyr resulting in >98% mortality after two applications. Mean western flower thrips adult mortality for spinosad was >95% whereas chlorfenapyr was >67% across all experiments. In general, the mean percent western flower thrips adult mortality for flonicamid ranged between 50% and 80%. Therefore, based on percent mortality, flonicamid was less effective against western flower thrips adults than spinosad or chlorfenapyr. Results from this study emphasize the importance of operational factors, especially spray volume and application frequency, in effectively managing insect pests. However, the effect of host plant architecture on spray volume and application frequency needs to be investigated. Proper use of insecticides against insect pests can reduce insecticide inputs and costs associated with labor. Citrus mealybugs and western flower thrips can be effectively managed using designated spray volumes and application frequencies, which will increase pest mortality and improve the suppression of pest populations.
Keywords: Citrus mealybug; Western flower thrips; Application frequency; Insecticide efficacy; Spray coverage and volume